Textile Innovations Delivery of Extension Services Programme for Rural Economic Empowerment and Development in Nigeria - K.O. , Ajila (Richtmann Publishing, 2021)
The study assessed textile innovations delivery of extension services programme in Nigeria, with a view to establishing its proficiency for rural economic empowerment and development. Explicitly, it examined the project techno-dynamics factor; analysed its economic costume and visibility variables. For this study 10 states and 40 blocks were purposively selected and 320 groups of villages within the selected blocks were visited. Stratified and simple random sampling procedure was used in selecting 15% of respondents from each group of villages, making 3,251 across the nation. While structured and pre-tested questionnaire was used in collecting quantitative data, individual interview schedule and Focus Group Discussions (FGDs) were applied in eliciting qualitative information from respondents. Data collected was summarized with the use of descriptive statistics viz; percentages, means and, frequency counts. Factor analysis was applied in isolating critical factors having relationship with proefficiency. The study isolated three important factors that were crucial to proficiency. These were textile innovations socio- technical (25.09%), accessibility (23.74%) and socio-economic (20.25%). It was concluded that the introduced textile innovations was proficient for rural economic empowerment and development. For proficiency, the finding suggests that inputs must be made available at the various extension centers, and on-farm textile producers must have direct access to market board without interference of product-coordinators. Received: 14 May 2021 / Accepted: 28 June 2021 / Published: 8 July 2021